AC/DC : [videorecording (DVD) live at River Plate - Mallet, David (Director) (Columbia, 2011)
In December 2009, AC/DC made a triumphant return to Buenos Aires where, throughout three sold out shows, the band was welcomed back to Argentina after a thirteen year absence by nearly 200,000 fans. Throughout their explosive set, the band performs such classics as You Shook Me All Night Long; Highway to Hell; and Back in Black.